Geography Teachers' Skills in Developing HOTS-Oriented Assessment Instruments in Metro City - Suhendro Suhendro; Dede Sugandi; Mamat Ruhimat (International Journal of Applied Business and International Management, 2021)
HOTS-oriented assessment is to improve students' high-level thinking skills in the classroom. The purpose of this study is to determine and analyze the skills of geography teachers in developing HOTS-oriented questions both theoretically and practically. The results show that their skills are theoretically and practically low. Teachers’ training to improve their competence in developing HOTS-oriented assessment instruments is necessary.